Stability of symptom-based subtypes in Sjogren’s disease - Xavier Mariette; Jacques-Eric Gottenberg; Jessica Tarn; Wan-Fai Ng; Dennis Lendrem; John Casement; Joe Scott Berry; Kyle Thompson (RMD Open)
Objectives The Newcastle Sjogren’s Stratification Tool (NSST) stratifies Sjogren’s disease patients into four subtypes. Understanding the stability of the subtypes is vital if symptom-based stratification is to be more broadly adopted. In this study, we stratify patients longitudinally to understand how symptom-based subtypes vary over time and factors influencing subtype change.Methods 274 patients from the United Kingdom Primary Sjögren’s Syndrome Registry (UKPSSR) with data permitting NSST subtype assignment from two study visits were included. The French Assessment of Systemic Signs and Evolution of Sjogren’s Syndrome (ASSESS) cohort (n=237) acted as an independent comparator. Group analyses of significant differences were performed, with logistic regression models used to assess covariates of subtype stability.Results UKPSSR and ASSESS cohorts showed a broadly similar proportion of subjects in each subtype and similar baseline clinical characteristics except body mass index (BMI). Several baseline characteristics differ significantly between the subtypes, most notably anti-Ro status and BMI. Subtype membership was reasonably stable in both cohorts with 60% and 57% retaining subtype. The high-symptom burden subtype was the most stable over time with 70% and 67% retaining subtype. Higher baseline probability score was the greatest predictor of subtype stability with higher C4 levels, antidepressant use, and a higher CCI score also predicting increased stability.Conclusion NSST subtype membership remains stable over time in a large proportion of patients. When subtype transition is associated with factors at baseline, it is most strongly associated with an uncertain subtype allocation. Our findings support the hypothesis that symptom-based subtypes reflect genuine pathobiological endotypes and therefore maybe important to consider in trial design and clinical management.